A CLASS OF UNIVALENT FUNCTION WITH FIXED FINITELY MANY COEFFICIENTS - Tehranchi, A.; Kulkarni, S. R.; Tuneski, Nikola (Matematichki Bilten, 2005)
In this paper a subclass of the class of univalent function is introduced by use of the Ruscheweyh derivative. Functions of this class have negative coefficients and have fixed finitely many coefficients. Necessary and sufficient conditions and extreme points for this class are provided. Also, it is shown that this classe is closed under convex linear combination and convolution and radius of starlikeness and convexity is found.